Numerical Modelling of Convective Wave using Fractional-Step Method - Yen Tey, Wah; Tang Tze Hou, Jared; Siang Kang, Hooi; ., . (International Journal of Engineering and Technology, 2018)
Wave equation is often solved independently without involving Continuity and momentum equations and this implies that the numerical simulation is restricted to wave phenomenon in static fluid. Meanwhile the available wave models are more suitable for the case in which the convective effect outweighs the local wave fluctuation. However, there are many fluid dynamics phenomena which involves equally significant effect of convective flow and wave disturbance, such as mountain waves, strong aeroacoustics wave and strong ocean waves. These flows need to be simulated by computational coupling. We have developed a solver using fractional step method for the construction of convective wave coupling algorithm. In our implementation, we model a flow across the wave-excited lid driven cavity as our case study, in which the model is to imitate the aerodynamic mountain wave. We found that the convective wave ratio plays a great role in affecting the velocity field of the fluid domain.Â